2013
DOI: 10.1089/adt.2013.548
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Heart Failure Models for the Evaluation of Chemical Probes and Drugs

Abstract: Heart failure is a complex disease that involves genetic, environmental, and physiological factors. As a result, current medication and treatment for heart failure produces limited efficacy, and better medication is in demand. Although mammalian models exist, simple and low-cost models will be more beneficial for drug discovery and mechanistic studies of heart failure. We previously reported that aristolochic acid (AA) caused cardiac defects in zebrafish embryos that resemble heart failure. Here, we showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…MoTP has been shown to cause melanocyte cell death in a tyrosinase-dependent manner (Yang et al [21]). MEK-I is interesting in that it caused notochord development defects ( Figure 1, Hawkins et al [22], Huang et al [16]), but only in early embryos. PTU also cause notochord distortion in early embryos, presumably due to its ability to chelate copper ions (also reported in Hawkins et al [22].…”
Section: Stronger Potency Of A11 Over Most Skin-lightening Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…MoTP has been shown to cause melanocyte cell death in a tyrosinase-dependent manner (Yang et al [21]). MEK-I is interesting in that it caused notochord development defects ( Figure 1, Hawkins et al [22], Huang et al [16]), but only in early embryos. PTU also cause notochord distortion in early embryos, presumably due to its ability to chelate copper ions (also reported in Hawkins et al [22].…”
Section: Stronger Potency Of A11 Over Most Skin-lightening Compoundsmentioning
confidence: 99%
“…Cosmetics 2018, 5, x FOR PEER REVIEW 3 of 14 Our lab has been using an established zebrafish heart failure model (Huang et al [16]) to look for compounds that could attenuate heart failure progression. Among the several positive compounds that were identified in the last few years, A11 and MEK-I were also able to cause significant reduction of black pigment in the zebrafish embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, incubation with Doxorubicin has proven as an excellent method for the induction of cardiomyopathy and heart failure in embryonic zebrafish within 4 days and adult zebrafish within 4 weeks after application to serve as a model for chronic heart failure [83,84]. Furthermore, zebrafish embryos treated with aristolochic acid develop cardiac hypertrophy and acute progression of heart failure eventually resulting in cessation of cardiac contractions 2 days after treatment [84,85]. This model was further validated by challenge with human heart failure drugs such as the b-blocker metoprolol and the ACE-inhibitor captopril, which attenuated heart failure in the aristolochic acid-treated zebrafish embryos [84].…”
Section: Cardiomyopathymentioning
confidence: 99%
“…This model was further validated by challenge with human heart failure drugs such as the b-blocker metoprolol and the ACE-inhibitor captopril, which attenuated heart failure in the aristolochic acid-treated zebrafish embryos [84]. By a SCS using both heart failure models and three small chemical libraries, Huang et al identified three drugs (mitogen-activated protein kinase inhibitor MEK-I, the chalacone derivate C25 and the phenolic compound A-11) that were able to suppress the heart failure phenotype in both, Doxorubicin and aristolochic acid-treated zebrafish embryos [85], suggesting that these compounds might target common pathways involved in heart failure.…”
Section: Cardiomyopathymentioning
confidence: 99%
“…Zebrafish embryos also offer the opportunity to test a variety of molecules through high throughput screening to facilitate the development of new therapies. 2,3 Although zebrafish embryos are outstanding as an in vivo model and have unique genetic tools, many human cardiovascular diseases occur at adulthood with a progressive pathogenesis. As such, the adult zebrafish model has been studied for its ability to model human cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%